2017
DOI: 10.1111/iju.13316
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Comment from Dr Kawahara to Prevention and treatment of symptoms associated with indwelling ureteral stents: A systematic review

Abstract: At nearly five decades since the first reported use of a ureteral stent by Zimskind et al., various materials and coatings have been developed to prevent ureteral stent complications, such as encrustation, incrustation, migration and infection.1 Although there are still ureteral stent-related symptoms, including urgency, dysuria, pain and hematuria, there is no widespread consensus on how to reduce ureteral stent complications. 2,3Betschart et al. carried out a systematic review of 107 articles on ureteral ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In cases of MUO, ureteral stenting allows percutaneous nephrostomy, an invasive procedure, to be avoided. Metallic ureteral stent insertion was associated with a superior and more durable response in comparison to polyurethane ureteral stent insertion [ 6 , 7 ]. Thus, metallic ureteral stent insertion can increase the time without nephrostomy in patients with MUO.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of MUO, ureteral stenting allows percutaneous nephrostomy, an invasive procedure, to be avoided. Metallic ureteral stent insertion was associated with a superior and more durable response in comparison to polyurethane ureteral stent insertion [ 6 , 7 ]. Thus, metallic ureteral stent insertion can increase the time without nephrostomy in patients with MUO.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that a polyurethane ureteral stent should be exchanged due to coloring and stone formation [ 8 , 9 ]. Thus, the use of a metallic stent can expected to reduce the need for unnecessary ureteral exchanges [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant ureteral obstruction (MUO) is often caused by advanced intra‐abdominal cancers. Effective management must be attempted, but the treatment policy is unclear 1–7 . The current management options are retrograde ureteral stent (RUS) placement or percutaneous nephrostomy under local anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Effective management must be attempted, but the treatment policy is unclear. 1 , 2 , 3 , 4 , 5 , 6 , 7 The current management options are retrograde ureteral stent (RUS) placement or percutaneous nephrostomy under local anesthesia. RUS is usually considered as the first treatment choice because of its low invasiveness.…”
Section: Introductionmentioning
confidence: 99%